Zero-formaldehyde high-fastness transparent waterproof fabric coating material and preparation method thereof
By using specific environmentally friendly raw materials and innovative process flows, combining composite emulsifiers and soft and hard monomers to form a coating material with a three-dimensional network structure, it solves the problem of zero formaldehyde, high fastness and transparency in the prior art, and realizes the problem of zero formaldehyde, high fastness and transparency. Waterproof fabric coating with high fastness, transparency and environmental protection.
Patent Information
- Application Number
- CN202411633533.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The existing waterproof fabric coating technology is difficult to take into account zero formaldehyde, high fastness and transparency, and poses health risks and aesthetic problems.
Using specific environmentally friendly raw materials and innovative process flows, the coating material with a three-dimensional network structure is formed through the combination of composite emulsifiers, soft and hard monomers, crosslinked monomers and hydrophilic monomers, to ensure high fastness and transparency.
A zero formaldehyde high-fast transparent waterproof fabric coating is achieved, meeting the comprehensive needs of environmental protection, functionality and aesthetics, reducing health risks and improving the durability of the coating.
Smart Images

Figure CN119465663A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material and a preparation method thereof. Background Art
[0002] With the improvement of people's living standards and the enhancement of environmental awareness, people's demand for clothing and textiles is not limited to basic wearing functions, but more attention is paid to their comfort, safety and environmental protection. Especially in outdoor sports, work in severe weather conditions or specific occupational needs, waterproof performance has become one of the important functions of textiles. Traditional waterproof fabric coatings often rely on formaldehyde-containing resins as adhesives to ensure the fastness and durability of the coating.
[0003] However, formaldehyde is a harmful substance that is harmful to human health. Long-term exposure may cause damage to the skin and nervous system or even cause cancer. At the same time, in the pursuit of environmental protection, existing waterproof coating technologies often find it difficult to balance the fastness and transparency of the coating. For example, although some water-based polyurethane coatings do not contain formaldehyde, their adhesion and wear resistance are poor, causing the coating to easily fall off or wear during use. In addition, the transparency of the coating is also a focus of consumer attention. Opaque coatings will affect the appearance of the fabric. In order to meet the market's demand for environmental protection and health, it is particularly important to develop a zero-formaldehyde, high-fastness and transparent waterproof fabric coating. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material and a preparation method thereof. By selecting specific environmentally friendly raw materials and innovative process flows, not only the generation of harmful substances such as formaldehyde is avoided, but also the high fastness and good transparency of the coating are ensured, thereby meeting the comprehensive needs of modern textiles in terms of environmental protection, functionality and aesthetics.
[0005] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0006] A zero-formaldehyde, high-fastness, transparent and waterproof fabric coating material, the coating material is composed of the following substances in parts by weight: 50-70 parts of water, 2-6 parts of a composite emulsifier, 15-25 parts of a soft monomer, 10-20 parts of a hard monomer, 1-4 parts of a hydrophilic monomer, 0.5-1 parts of a cross-linking monomer, 4-6 parts of a cross-linking aid, 0.1-0.5 parts of an initiator, 0.05-0.3 parts of an oxidant, 0.03-0.2 parts of a reducing agent, 0.1-1 parts of a defoaming agent, 0.1-0.4 parts of a bactericide, and 0.5-4 parts of a pH regulator; the composite emulsifier is composed of an anionic emulsifier and a nonionic emulsifier in a mass ratio of 1:1-2; the hydrophilic monomer is composed of an acid monomer and a hydroxyl-containing monomer in a mass ratio of 1:4-8.
[0007] Preferably, the anionic emulsifier is one of sodium dodecyl sulfate, sodium C10-C16 alkyl alcohol ether sulfate, and sodium dodecyl diphenyl ether disulfonate; the nonionic emulsifier is one of allyl alcohol polyoxyethylene ether, methyl allyl alcohol polyoxyethylene ether, and polyoxyethylene sorbitan ester.
[0008] Preferably, the soft monomer is one or more of ethyl acrylate, butyl acrylate and isooctyl acrylate.
[0009] Preferably, the hard monomer is one or more of methyl methacrylate, styrene and acrylonitrile.
[0010] Preferably, the acid monomer is one of acrylic acid, methacrylic acid and maleic acid; the hydroxyl-containing monomer acid monomer is one or more of 2-hydroxyethyl methacrylate, hydroxyethyl acrylate and hydroxyethyl methacrylate.
[0011] Preferably, the cross-linking monomer is one or more of diacetone acrylamide, trimethylolpropane triacrylate, and glycidyl methacrylate.
[0012] Preferably, the cross-linking aid is one of vinyltrimethoxysilane and 1,2,3,4-tetracarboxylic acid butane; the initiator is one of potassium persulfate and sodium persulfate; the oxidant is tert-butyl hydroperoxide; the reducing agent is sodium metabisulfite; the defoamer is one or more of Dow Corning silicone defoamer AFE-0020, Xingrui polyether / silicone defoamer SGR1832, and Zhonglianban silicone defoamer B-313; the bactericide is one or more of Kathon, benzisothiazolinone, and methylphosphonium sulfate tetrahydroxy; the pH adjuster is one or more of sodium bicarbonate, disodium hydrogen phosphate, and sodium hydroxide.
[0013] The preparation method of the zero-formaldehyde high-fastness transparent waterproof fabric coating material comprises the following steps:
[0014] S01, preparing an emulsion in an emulsifying kettle: adding 46-52 parts of water, 2.8-4.4 parts of a composite emulsifier, all soft monomers, hard monomers, hydrophilic monomers, cross-linking monomers and cross-linking aids into an emulsifying kettle in order and stirring to obtain an emulsion, and adding water to an initiator to prepare two initiator solutions, namely a first initiator solution and a second initiator solution;
[0015] S02, adding the remaining water and the remaining composite emulsifier into the reaction kettle and stirring, heating to 74-78° C., adding the above 8%-20% emulsion and stirring, and then adding the first initiator;
[0016] S03, continue to raise the temperature to 82-86°C, and simultaneously drop the remaining emulsion and the second initiator for 3.5-4 hours. After the addition is completed, keep warm for 1.5-2 hours;
[0017] S04, cool down to 75±2℃, add oxidant and reductant simultaneously, the addition time is 10~20min;
[0018] S05, quickly cool down to 45±5℃, add defoamer and bactericide respectively, the adding time is 10-20min;
[0019] S06. Add pH regulator to adjust the pH value of the emulsion to 7-9. After stabilization, filter the material with a 250 mech filter bag.
[0020] Preferably, the stirring methods in step S01 and step S02 are both electromagnetic stirring, and the stirring frequency in step S01 is 20-40 Hz, and the stirring frequency in step S02 is 20-30 Hz.
[0021] Preferably, in step S01, the content of the initiator in the first initiator accounts for 40% to 60% of the total initiators, and the first initiator is prepared by adding 0.3-0.5 parts of water; the content of the initiator in the second initiator accounts for 40% to 60% of the total initiators, and the second initiator is prepared by adding 1.2-2 parts of water.
[0022] The present invention provides a zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material and a preparation method thereof, which has the following advantages over the prior art:
[0023] (1) The present invention avoids the use of amide cross-linking monomers, formaldehyde-containing reducing agents, formaldehyde-containing bactericides, and amino-containing pH regulators by not adding formaldehyde or any components that easily release formaldehyde, thereby enabling the textile waterproof coating to avoid the health risks associated with formaldehyde and meeting consumers' demand for safe textiles;
[0024] (2) The present invention can adjust the flexibility and hardness of the polymer chain by selecting a specific soft monomer and hard monomer compound system. The soft monomer (such as butyl acrylate) provides flexibility and extensibility, while the hard monomer (such as styrene) increases the rigidity and strength of the polymer chain. The combination of soft and hard monomers allows the coating to have sufficient mechanical strength while maintaining flexibility. Furthermore, the addition of cross-linking monomers, hydrophilic monomers (acid monomers and hydroxyl-containing monomers) and cross-linking aids (silane coupling agents) helps to form a three-dimensional network structure, which can significantly improve the cohesion and tensile strength of the coating and improve the fastness of the coating. At the same time, the use of a composite emulsifier system (a combination of anionic and non-ionic emulsifiers) helps to form stable emulsion particles. These stable emulsion particles can form a uniform and highly adhesive coating on the surface of the fabric, thereby improving the durability and fastness of the coating.
[0025] (3) The present invention adopts a composite emulsifier system, including an anionic emulsifier (such as sodium dodecyl sulfate) to provide negative charge, which helps to form negatively charged emulsion particles and increase the stability of the emulsion; a nonionic emulsifier (such as polyoxyethylene sorbitan ester) provides a good emulsification effect in a wide pH range and reduces the emulsion destruction caused by pH changes; this composite emulsifier can more effectively reduce interfacial tension. When the emulsifier concentration is increased, it promotes the uniform dispersion of the oil-water mixture to form polymer particles with small particle size and high transparency, thereby increasing the transparency of the emulsion and achieving the purpose of subsequently forming a transparent waterproof coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] Preparation of fabric coating materials:
[0030] S01, preparing an emulsion in an emulsifying kettle: adding 52 parts of water, 2.2 parts of sodium lauryl sulfate, 2.2 parts of methyl allyl alcohol polyoxyethylene ether, 12 parts of butyl acrylate, 6 parts of isooctyl acrylate, 9.5 parts of styrene, 0.6 parts of acrylic acid, 3.4 parts of hydroxyethyl acrylate, 0.6 parts of diacetone acrylamide, and 2 parts of vinyl trimethoxy silane into the emulsifying kettle in this order, stirring at a stirring frequency of 20 Hz to obtain an emulsion; then preparing two initiator solutions, adding 0.3 parts of water and 0.08 parts of sodium persulfate to the first initiator solution, and adding 1.2 parts of water and 0.12 parts of sodium persulfate to the second initiator solution;
[0031] S02, add 5 parts of water, 0.3 parts of sodium lauryl sulfate and 0.3 parts of methyl allyl alcohol polyoxyethylene ether into the reactor, heat it to 75°C, add 8% of the mass of the emulsion as the seed emulsion, stir at a stirring frequency of 20 Hz for 5 minutes, and add the first stage initiator;
[0032] S03, continue to raise the temperature to 83°C, and simultaneously drop the remaining emulsion and the second stage initiator for 3.5 hours. After the dropwise addition is completed, keep the temperature for 2 hours;
[0033] S04, cool to 75°C, add 0.25 parts of tert-butyl hydroperoxide and 0.15 parts of sodium metabisulfite simultaneously, the addition time is 10 minutes;
[0034] S05, quickly cool down to 45°C, add 0.6 parts of Dow Corning silicone defoamer AFE-0020 and 0.2 parts of methylphosphonium sulfate tetrahydroxy fungicide, respectively, and the addition time is 10 minutes;
[0035] S06. Add 1 part of 32.5% sodium hydroxide pH regulator, and filter the material with a 250 mech filter bag after stabilization to obtain a fabric coating material.
[0036] Embodiment 2:
[0037] Preparation of fabric coating materials:
[0038] S01. Prepare an emulsion in an emulsifying kettle: add 54 parts of water, 2 parts of sodium dodecyl sulfate, 2 parts of Tween 80, 10 parts of ethyl acrylate, 10 parts of isooctyl acrylate, 5 parts of methyl methacrylate, 0.8 parts of methacrylic acid, 3.4 parts of 2-hydroxyethyl methacrylate, 1 part of trimethylolpropane triacrylate, and 3 parts of 1,2,3,4-tetracarboxylic acid butane into the emulsifying kettle in this order and stir to obtain an emulsion; wherein the stirring frequency of the emulsion is 20 Hz; then prepare two initiator solutions, wherein 0.3 parts of water and 0.08 parts of sodium persulfate are added to the first initiator solution, and 1.2 parts of water and 0.12 parts of sodium persulfate are added to the second initiator solution.
[0039] S02, add 4 parts of water, 0.5 parts of sodium dodecyl sulfate and 0.5 parts of Tween 80 into the reactor, heat it to 75°C, add 10% of the mass of the emulsion as the seed emulsion, stir for 5 minutes, and add the first stage initiator;
[0040] S03, continue to raise the temperature to 83°C, and simultaneously drop the remaining emulsion and the second stage initiator for 3.5 hours. After the dropwise addition is completed, keep the temperature for 1.5 hours;
[0041] S04, cool to 75°C, add 0.25 parts of tert-butyl hydroperoxide and 0.15 parts of sodium metabisulfite simultaneously, the addition time is 10 minutes;
[0042] S05, quickly cool down to 45°C, add 0.3 parts of Xingrui polyether / silicone defoamer SGR1832 and 0.2 parts of Kasson fungicide, respectively, and the addition time is 10 minutes;
[0043] S06. Add 1.2 parts of 32.5% sodium hydroxide as a pH regulator, and after stabilization, filter the material with a 250 mech filter bag to obtain a fabric coating material.
[0044] Embodiment 3:
[0045] Preparation of fabric coating materials:
[0046] S01. Prepare an emulsion in an emulsifier: add 46 parts of water, 1.3 parts of sodium lauryl alcohol ether sulfate, 1.5 parts of allyl alcohol polyoxyethylene ether, 6 parts of butyl acrylate, 14 parts of isooctyl acrylate, 9 parts of styrene, 0.6 parts of acrylic acid, 3.4 parts of hydroxyethyl methacrylate, 0.8 parts of glycidyl methacrylate, and 2 parts of vinyl trimethoxy silane into the emulsifier and stir to obtain an emulsion. The stirring frequency of the emulsion is 20 Hz. Then prepare two initiator solutions, add 0.3 parts of water and 0.08 parts of potassium persulfate to the first initiator solution, and 1.2 parts of water and 0.12 parts of potassium persulfate to the second initiator solution.
[0047] S02. Add 10 parts of water, 0.65 parts of sodium lauryl sulfate and 0.8 parts of methyl allyl alcohol polyoxyethylene ether into the reactor, heat to 75°C, add 8% of the mass of the emulsion as the seed emulsion, stir for 5 minutes, and add the first stage initiator.
[0048] S03, continue to raise the temperature to 83°C, and simultaneously drop the remaining emulsion and the second stage initiator. The dropping time is 4 hours, and after the dropping is completed, keep warm for 1.5 hours.
[0049] S04, cool down to 75°C, and simultaneously add 0.2 parts of tert-butyl hydroperoxide and 0.15 parts of sodium metabisulfite, the addition time is 10 minutes.
[0050] S05. Rapidly cool down to 45°C, add 0.5 parts of Zhonglianban silicone defoamer B-313 and 0.1 parts of benzisothiazolinone fungicide respectively, and the addition time is 10 minutes.
[0051] S06. Add 1.3 parts of 32.5% sodium hydroxide as a pH regulator, and filter the material with a 250 mech filter bag after stabilization to obtain a fabric coating material.
[0052] Comparative Example 1:
[0053] Preparation of fabric coating materials:
[0054] S01. Prepare an emulsion in an emulsifying kettle: add 52 parts of water, 4.4 parts of sodium dodecyl sulfate, 12 parts of butyl acrylate, 5.5 parts of isooctyl acrylate, 9.5 parts of styrene, 0.6 parts of acrylic acid, 3.4 parts of hydroxyethyl acrylate, 0.6 parts of hydroxymethyl acrylamide, and 2 parts of vinyl trimethoxy silane in the order of stirring to obtain an emulsion. The stirring frequency of the emulsion is 20 Hz. Then prepare two initiator solutions, the first initiator solution is added with 0.3 parts of water and 0.08 parts of ammonium persulfate, and the second initiator solution is added with 1.6 parts of water and 0.12 parts of ammonium persulfate.
[0055] S02. Add 5 parts of water and 0.65 parts of sodium dodecyl sulfate into the reactor, heat it to 75°C, add 12% of the mass of the emulsion as the seed emulsion, stir for 5 minutes, and add the first stage initiator.
[0056] S03, continue to raise the temperature to 83°C, and simultaneously drop the remaining emulsion and the second stage initiator. The dropping time is 3.5 hours, and keep warm for 2 hours after the dropping is completed.
[0057] S04, cool down to 75°C, add 0.25 parts of tert-butyl hydroperoxide and 0.2 parts of sodium formaldehyde bisulfite simultaneously, and the addition time is 10 minutes.
[0058] S05. Rapidly cool down to 45°C, add 0.6 parts of Dow Corning silicone defoamer AFE-0020 and 0.2 parts of methylphosphonium sulfate tetrahydroxy fungicide, respectively, and the addition time is 10 minutes.
[0059] S06. Add 1 part of 20% ammonia water as a pH regulator, and after stabilization, filter the material with a 250 mech filter bag to obtain a fabric coating material.
[0060] Comparative Example 2:
[0061] Preparation of fabric coating materials:
[0062] S01. Prepare an emulsion in an emulsifying kettle: add 52 parts of water, 2 parts of sodium dodecyl diphenyl ether disulfonate, 3 parts of methyl allyl alcohol polyoxyethylene ether, 12 parts of butyl acrylate, 5 parts of isooctyl acrylate, 7 parts of acrylonitrile, 0.8 parts of acrylic acid, 4 parts of hydroxyethyl acrylate, 0.6 parts of hydroxymethyl acrylamide, and 2 parts of vinyl trimethoxy silane in the order of stirring to obtain an emulsion. The stirring frequency of the emulsion is 20 Hz. Then prepare two initiator solutions, add 0.5 parts of water and 0.2 parts of ammonium persulfate to the first initiator solution, and add 3 parts of water and 0.15 parts of ammonium persulfate to the second initiator solution.
[0063] S02. Add 5 parts of water, 0.5 parts of sodium dodecyl diphenyl ether disulfonate and 0.3 parts of methyl allyl alcohol polyoxyethylene ether into the reactor. After heating to 75°C, add 10% of the mass of the emulsion as the seed emulsion, stir for 5 minutes, and add the first stage initiator.
[0064] S03, continue to raise the temperature to 83°C, and simultaneously drop the remaining emulsion and the second stage initiator. The dropping time is 4 hours, and keep warm for 2 hours after the dropping is completed.
[0065] S04, cool down to 75°C, and simultaneously add 0.2 parts of tert-butyl hydroperoxide and 0.15 parts of sodium formaldehyde bisulfite, the addition time is 10 minutes.
[0066] S05. Rapidly cool down to 45°C and add 0.6 parts of Dow Corning silicone defoamer AFE-0020 respectively, with the addition time of 10 minutes.
[0067] S06. Add 1 part of 20% ammonia water as a pH regulator, and after stabilization, filter the material with a 250 mech filter bag to obtain a fabric coating material.
[0068] Detection:
[0069] The fabric coating materials prepared in the above Examples 1-3 and Comparative Examples 1-2 were tested with reference to the following standards:
[0070] (1) Coating transmittance test standard: GB / T 2410-2008;
[0071] (2) Formaldehyde test standard: GB 18401-2010 (formaldehyde content not exceeding 20 mg / kg can meet the requirements for textile products for infants and young children);
[0072] (3) Textile waterproof test standard: GB / T 4745-2012;
[0073] (4) Coating fastness test standard: GB / T 19089-2012;
[0074] The specific test results are shown in Table 1 below:
[0075] Table 1
[0076] Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Emulsion particle size (nm) 66.78 71.23 68.73 113.42 136.52 Particle size distribution index 0.034 0.035 0.026 0.025 0.038 Viscosity(mpa.s) 845 800 860 785 638 Light transmittance (%) 95 95 95 70 85 pH 7.52 7.65 7.33 7.27 7.63 Solid content (%) 56.73 55.23 58.34 50.24 53.93 Formaldehyde (ppm) 6 8 8 102 87 Waterproof effect (points) 90 90 90 80 80 Wear resistance (grade) 0 0 0 1 1
[0077] As can be seen from Table 1, the materials prepared in Examples 1-3 have the characteristics of high fastness, zero formaldehyde release, transparency and waterproofness.
[0078] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A zero formaldehyde, high-fastness, transparent and waterproof fabric coating material, characterized in that: The coating material is composed of the following substances in parts by weight: 50-70 parts of water, 2-6 parts of composite emulsifier, 15-25 parts of soft monomer, 10-20 parts of hard monomer, 1-4 parts of hydrophilic monomer, 0.5-1 parts of cross-linking monomer, 4-6 parts of cross-linking auxiliary agent, 0.1-0.5 parts of initiator, 0.05-0.3 parts of oxidant, 0.03-0.2 parts of reducing agent, 0.1-1 parts of defoaming agent, 0.1-0.4 parts of bactericide, and 0.5-4 parts of pH regulator; The composite emulsifier is composed of anionic emulsifier and nonionic emulsifier in a mass ratio of 1:1-2; the hydrophilic monomer is composed of acid monomer and hydroxyl-containing monomer in a mass ratio of 1:4-8.
2. The zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material according to claim 1, characterized in that: The anionic emulsifier is one of sodium lauryl sulfate, sodium C10-C16 alkyl alcohol ether sulfate, and sodium dodecyl diphenyl ether disulfonate; the nonionic emulsifier is one of allyl alcohol polyoxyethylene ether, methyl allyl alcohol polyoxyethylene ether, and polyoxyethylene sorbitol ester.
3. The zero formaldehyde high-fastness transparent waterproof fabric coating material according to claim 1, characterized in that: The soft monomer is composed of one or more of ethyl acrylate, butyl acrylate and isooctyl acrylate.
4. The zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material according to claim 1, characterized in that: The hard monomer is composed of one or more of methyl methacrylate, styrene and acrylonitrile.
5. The zero formaldehyde high-fastness transparent waterproof fabric coating material according to claim 1, characterized in that: The acid monomer is one of acrylic acid, methacrylic acid and maleic acid; the hydroxyl-containing monomer acid monomer is one or more of 2-hydroxyethyl methacrylate, hydroxyethyl acrylate and hydroxyethyl methacrylate.
6. The zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material according to claim 1, characterized in that: The cross-linking monomer is one or more of diacetone acrylamide, trimethylolpropane triacrylate, and glycidyl methacrylate.
7. The zero-formaldehyde, high-fastness, transparent and waterproof fabric coating material according to claim 1, characterized in that: The cross-linking auxiliary agent is one of vinyl trimethoxysilane and 1,2,3,4-tetracarboxylic acid butane; the initiator is one of potassium persulfate and sodium persulfate; the oxidant is tert-butyl hydroperoxide; the reducing agent is sodium metabisulfite; the defoamer is one or more of Dow Corning silicone defoamer AFE-0020, Xingrui polyether / silicone defoamer SGR1832, and Zhonglianban silicone defoamer B-313; the bactericide is one or more of Kathon, benzisothiazolinone, and methylphosphonium sulfate tetrahydroxy; the pH adjuster is one or more of sodium bicarbonate, disodium hydrogen phosphate, and sodium hydroxide.
8. A method for preparing a zero-formaldehyde, high-fastness, transparent, waterproof fabric coating material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S01, preparing an emulsion in an emulsifying kettle: adding 46-52 parts of water, 2.8-4.4 parts of a composite emulsifier, all soft monomers, hard monomers, hydrophilic monomers, cross-linking monomers and cross-linking aids into an emulsifying kettle in order and stirring to obtain an emulsion, and adding water to an initiator to prepare two initiator solutions, namely a first initiator solution and a second initiator solution; S02, adding the remaining water and the remaining composite emulsifier into the reaction kettle and stirring, heating to 74-78° C., adding the above 8%-20% emulsion and stirring, and then adding the first initiator; S03, continue to raise the temperature to 82-86°C, and simultaneously drop the remaining emulsion and the second initiator for 3.5-4 hours. After the addition is completed, keep warm for 1.5-2 hours; S04, cool down to 75±2℃, add oxidant and reductant simultaneously, the addition time is 10~20min; S05, quickly cool down to 45±5℃, add defoamer and bactericide respectively, the adding time is 10-20min; S06. Add pH regulator to adjust the pH value of the emulsion to 7-9. After stabilization, filter the material with a 250 mech filter bag.
9. The preparation method according to claim 8, characterized in that: The stirring methods in step S01 and step S02 are both electromagnetic stirring, and the stirring frequency in step S01 is 20-40 Hz, and the stirring frequency in step S02 is 20-30 Hz.
10. The preparation method according to claim 8, characterized in that: In the step S01, the content of the initiator in the first initiator accounts for 40% to 60% of the total initiator, and the first initiator is prepared by adding 0.3-0.5 parts of water; the content of the initiator in the second initiator accounts for 40% to 60% of the total initiator, and the second initiator is prepared by adding 1.2-2 parts of water.